1977
DOI: 10.1128/aac.11.3.500
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical and Biochemical Studies of Yeasts After In Vitro Exposure to Miconazole

Abstract: Yeast cells exposed to different doses of the antimycotic agent miconazole revealed important cytochemical changes in the topographic distribution of the phosphatases. A strong effect was observed on the behavior of oxidative and peroxidative enzymes. Decreased cytochrome c oxidase and peroxidase activity and increased catalase activity were seen after treatment with a fungistatic dose ofmiconazole, whereas a complete disappearance ofthese enzymes was observed after treatment with a minimal fungicidal dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 42 publications
2
32
1
Order By: Relevance
“…6A). On the other hand, the results do not exclude a mechanism involving NO sensitization due to lanosterol 14␣-demethylase inhibition as previously suggested for clotrimazole sensitization of C. albicans to hydrogen peroxide (50) or the direct inhibition of membrane-bound ATPases and cytochrome oxidase, as well as the synthesis of mitochondrial and peroxisomal enzymes including peroxidase and catalase (8,9,30). Indeed, antibiotic synergy between imidazoles and NO-releasing diazeniumdiolates was previously reported for Candida (34) and may also be explained by NOD-independent mechanisms since the agents inhibited NOD weakly.…”
Section: Discussionmentioning
confidence: 65%
“…6A). On the other hand, the results do not exclude a mechanism involving NO sensitization due to lanosterol 14␣-demethylase inhibition as previously suggested for clotrimazole sensitization of C. albicans to hydrogen peroxide (50) or the direct inhibition of membrane-bound ATPases and cytochrome oxidase, as well as the synthesis of mitochondrial and peroxisomal enzymes including peroxidase and catalase (8,9,30). Indeed, antibiotic synergy between imidazoles and NO-releasing diazeniumdiolates was previously reported for Candida (34) and may also be explained by NOD-independent mechanisms since the agents inhibited NOD weakly.…”
Section: Discussionmentioning
confidence: 65%
“…Sud and Feingold (290) discovered that the fungistatic potentials of miconazole and clotrimazole were abrogated in reduced oxygen tensions. Miconazole also has been shown to adversely affect cytochrome and peroxidase activity in cells of C. albicans and Saccharomyces cerevisiae (69). Ketoconazole blocks the transport of electrons in the respiratory chain of C. albicans (273,311).…”
Section: Proposed Modes Of Action Of Antifungal Azole Derivativesmentioning
confidence: 99%
“…Furthermore, in fungi and yeast, azole treatment leads to an increase in the endogenous production of reactive oxygen species (ROS) (12,25). For example, in Candida albicans and Saccharomyces cerevisiae, the miconazole inhibition of cytochrome c oxidase, peroxidase, and catalase has been reported to be responsible for a high level of ROS production (3,4). It has also been reported that clotrimazole inhibition of Plasmodium falciparum hemoperoxidase leads to ROS accumulation in this protozoan pathogen (26).…”
mentioning
confidence: 99%